2011
DOI: 10.1007/s00415-011-5969-1
|View full text |Cite
|
Sign up to set email alerts
|

The health-related, social, and economic consequences of parkinsonism: a controlled national study

Abstract: Parkinson's disease (PD) and atypical parkinsonism (AP) cause a significant socioeconomic burden, but there is insufficient information about the total disease burden at a national level. Thus, the goal of this study was to estimate the excess direct and indirect costs of PD and AP in a national sample. Using records from the Danish National Patient Registry (1997-2007), 13,400 PD and 647 AP patients were identified and compared with, respectively, 53,600 and 2,588 control cases randomly selected with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 57 publications
3
37
1
Order By: Relevance
“…The disorders have large direct and indirect costs for society (Jennum et al, 2011). PD is the second most common neurodegenerative disease after Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…The disorders have large direct and indirect costs for society (Jennum et al, 2011). PD is the second most common neurodegenerative disease after Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the area of environmental resources, we find studies examining economic effects of PD or those having Parkinsonian symptoms. 14,15 More specifically, a recent study 16 showed that people with PD or having Parkinsonian symptoms were using medicine to a higher extent and had more than three times higher medical costs than matched controls. Moreover, they were more likely to receive welfare payments.…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect of the involvement of spouses is the increased use of health-care services and social factors. This was also observed in other neurological diseases [13,14,15,16]. This observation requires further evaluation but we believe that the neurological deficits and common pattern of risk association is involved in the increased health-care use and social effect to partners.…”
Section: Discussionmentioning
confidence: 90%
“…3 and 4). Such limitations have been described in other chronic and progressive disorders, such as multiple sclerosis [17], Parkinsonism [18], and narcolepsy [19], although these are associated with long-lasting and pre-diagnostic courses. The pre-diagnostic health effects cannot be attributed to the diagnosis but are probably due to comorbid conditions associated with, or causing, the polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation